Intestinal SURF4 is essential for apolipoprotein transport and lipoprotein secretion - Chun-Guang Guo; Rui Sun; Xiao Wang; Ye Yuan; Yan Xu; Shihan Li; Xueting Sun; Jue Wang; Xinli Hu; Tiannan Guo; Xiao-Wei Chen; Rui-Ping Xiao; et al. (Elsevier, 2024)
Objective: Lipoprotein assembly and secretion in the small intestine are critical for dietary fat absorption. Surfeit locus protein 4 (SURF4) serves as a cargo receptor, facilitating the cellular transport of multiple proteins and mediating hepatic lipid secretion in vivo. However, its involvement in intestinal lipid secretion is not fully understood. In this study, we investigated the role of SURF4 in intestinal lipid absorption. Methods: We generated intestine-specific Surf4 knockout mice and characterized the phenotypes. Additionally, we investigated the underlying mechanisms of SURF4 in intestinal lipid secretion using proteomics and cellular models. Results: We unveiled that SURF4 is indispensable for apolipoprotein transport and lipoprotein secretion. Intestine-specific Surf4 knockout mice exhibited ectopic lipid deposition in the small intestine and hypolipidemia. Deletion of SURF4 impeded the transport of apolipoprotein A1 (ApoA1), proline-rich acidic protein 1 (PRAP1), and apolipoprotein B48 (ApoB48) and hindered the assembly and secretion of chylomicrons and high-density lipoproteins. Conclusions: SURF4 emerges as a pivotal regulator of intestinal lipid absorption via mediating the secretion of ApoA1, PRAP1 and ApoB48.